Comparison of traditional and online education in airway management - Yazıcı, Mümin Murat; Ataş, İsmail; Güler, Enes; Bilir, Özlem (International Journal of Research in Medical Sciences, 2023)
Background: Endotracheal intubation is commonly used to maintain the airway during airway management, but it requires skill and experience, so standard endotracheal intubation performed by beginner managers carries a high risk of failure. This study was conducted based on the hypothesis that there are differences between the traditional and online education models in terms of learning and skill development in situations requiring basic skills, and it aimed to compare the traditional and online education models to evaluate endotracheal intubation learning and skills. Methods: This single-centre, prospective study aimed to evaluate the endotracheal intubation performance of volunteers. The research involved examining the endotracheal intubation experience of fourth-year medical school students who completed their education either traditionally or online at the Recep Tayyip Erdogan university simulation-based learning centre (RSIM). Approval was obtained before commencement from the local ethical committee (decision no. 2023/03, E-40465587-050.01.04-572). Results: Mean time for successful intubation in the traditional and online education models evaluated was statistically significant at the non-difficult (p=0.005), moderately difficult (p=0.007) and difficult airway (p=0.014) levels. Conclusions: Traditional and online education models affect endotracheal intubation ability. In endotracheal intubation with either a direct or a video laryngoscope, the traditional education model offered a more successful experience than the online education model. In addition, skills with the video laryngoscope were stronger in novice users than with the direct laryngoscope.